Pengaruh dosis pupuk urea terhadap pertumbuhan dan produksi plasma nutfah padi lokal asal aceh - Anhar, Ridwan; Hayati, Erita; Efendi, Efendi (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala)
This study aims to determine the effect of Urea fertilizer on the growth and production of local rice germplasm from Aceh. The results showed that treatment of Urea very significant effect on the number of tillers at the age of 60 days after planting, and significantly affected the number of seedlings 45 days after planting. Growth and yield the best found in the treatment of urea 0.65 g pot-1 (200 kg ha-1). Varieties very significant effect on plant height age of 30, 45 and 60 days after planting, tillering, number of tillers at the age of 45 and 60 days after planting, life begins to flower, the percentage of grain contains, the percentage of empty grains, 1,000 grain weight, yield per plot and yield per hectare. Continously varieties significantly affected the number of seedlings 15 days after planting. Productivity of rice plants is best found in the varieties Sipirok 9.58 tons ha-1. There is no real interaction between the urea treatment of all varieties of variable growth and yield of rice plants.